Legal Framework of Micro and Small Businesses in Indonesia for Achieving Empowerment and Legal Protection - Kuahaty, Sarah Selfina; Hetharie, Yosia (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to identify, analyze, and discover efforts to facilitate business ease, empowerment, and protection for micro and small business operators in the Maluku Province through effective local legal regulations. Micro and small businesses play a vital role in supporting national development and enhancing the country's economy. Therefore, micro and small businesses need to be continuously developed to remain viable and competitive in the global trade arena. One of the measures to ensure the sustainability of micro and small businesses is through effective legal regulations that address various challenges faced by them. These legal regulations encompass not only national legal aspects but also local legal frameworks, including those in the Maluku Province. This research constitutes sociolegal research using primary and secondary data obtained through literature review and interviews. Based on the research findings, it is evident that the legal regulations for micro and small businesses in Maluku, both at the provincial and municipal levels, are not sufficiently effective in realizing ease of doing business, empowerment, and protection for micro and small business operators. The ineffectiveness of local legal provisions in Maluku is attributed to various issues in their content. These issues include discrepancies in regulations compared to other legal provisions, overlapping jurisdiction between the provincial and municipal governments, and even the central government's authority in regulating medium-sized businesses. Furthermore, legal gaps and unclear content lead to normative ambiguity, ultimately affecting the implementation of micro-business development and empowerment, which does not proceed smoothly.